Nonreciprocal optical response of helical periodic structures of plasma spheres in a static magnetic field - A. Christofi; N. Stefanou (Physical Review B, 2013)
A detailed and rigorous theoretical investigation of the optical properties of a generic three-dimensional chiral structure of plasma spheres, without and under the action of an external static uniform magnetic field, is presented. Corresponding photonic band diagrams in conjunction with relevant transmission spectra, calculated by the full electrodynamic layer-multiple-scattering method properly extended to the case of gyrotropic spherical scatterers, are discussed in the light of the theory of nonsymmorphic space groups. This analysis provides a consistent interpretation of some remarkable features and effects like Dirac points, polarization-dependent transmission, as well as band splitting and non-reciprocal optical response that emerge as a result of time-reversal-symmetry breaking, induced by the external static magnetic field, and the lack of space-inversion symmetry in the crystal.